Reduction method for preparing superfine cobalt powder by hydrazine hydrate - HE XIANDA; SHI YUJIE; SU TAOGUI; WANG QIN; MA LIN; CHEN YANHONG (2013)
The invention is applied to the field of metal micro-particle preparation, and provides a reduction method for preparing superfine cobalt powder by hydrazine hydrate. The method comprises the following steps of: preparing mixed solution of cobalt salt and a dispersing agent; preparing cobalt salt complex; and preparing cobalt powder. According to the reduction method provided by the invention for preparing superfine cobalt powder by hydrazine hydrate, firstly, the hydrazine hydrate is added in order to form hydrazine hydrate-cobalt complex, the hydrazine hydrate-cobalt complex is subject to the pH (potential of hydrogen) adjustment and then is added in hydrazine hydrate for reacting, in this way, the reaction potential barrier of hydrazine hydrate and cobalt salt is greatly reduced, the reaction of hydrazine hydrate and cobalt becomes completely and fully, the production efficiency is improved, the production cost is reduced, the prepared cobalt powder is high in purity and is widely used in the industrial fi